From Self-Fulfilment to Survival of the Fittest Work in European Cinema from the 1960s to the Present - Mazierska, Ewa (Berghahn Books, 2015)
Contrary to the assumption that Western and Eastern European economies and cinemas were very different from each other, they actually had much in common. After the Second World War both the East and the West adopted a mixed system, containing elements of both socialism and capitalism, and from the 1980s on the whole of Europe, albeit at an uneven speed, followed the neoliberal agenda. This book examines how the economic systems of the East and West impacted labor by focusing on the representation of work in European cinema. Using a Marxist perspective, it compares the situation of workers in Western and Eastern Europe as represented in both auteurist and popular films, including those of Tony Richardson, Lindsay Anderson, Jean-Luc Godard, Andrzej Wajda, Dušan Makavejev, Jerzy Skolimowski, the Dardenne Brothers, Ulrich Seidl and many others.